Pengaruh Influencer Marketing, Content Marketing, Online Consumer Review Terhadap Keputusan Pembelian Studi Pada Mahasiswa Kota Malang Pembeli Moisturizer Glad To Glow (G2G) - Putri Zakiyah; Muhammad Agus Salim; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to examine the effects of influencer marketing, content marketing, and online consumer reviews on purchase decisiouns among university students in Malang City who have purchased Glad2Glow moisturizer products. This study employs a quantitative method using multiple lineaar regression analysis. Data were collected from 110 respondentss through a questionnaire, consisting of university students in Malang City who had previously purchased Glad2Glow moisturizer. Instrument testing included validity and reliability tests, as well as normality testing, classical assumption tests, F-tests, t-tests, and coefficient of determination analysis to evaluate the proposed hypotheses. The findings indicate that, both individually and simultaneously, influencer marketing, content marketing, and online consumer reviews have a significant effect on purchase decisions. Among these variables, influencer marketing demonstrates the strongest influence, suggesting that students tend to be more responsive to recommendations and the perceived credibility of influencers when making purchasing decisions for skincare products. Keywords: Influencer Marketing, Content Marketing, Online Consumer Review, Keputusan Pembelian, Glad2Glow